2017
DOI: 10.1186/s13643-017-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with E-Oral Health care in rural and remote settings: a systematic review protocol

Abstract: BackgroundIndividuals living in rural and remote settings face oral health problems and access-to-care barriers due to the shortage of oral health care providers in these areas, geographic remoteness, lack of appropriate infrastructure and lower socio-economic status. E-Oral Health technology could mitigate these barriers by providing the delivery of some aspects of health care and exchange of information across geographic distances. This review will systematically evaluate the literature on patient satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The reported advantages include lower financial costs, high patient satisfaction, better rural access, decreased waiting times and fewer missed appointment. [2][3][4][5][6][7] There is less available evidence from primary care; however, there are positive findings in primary care chronic disease management. [8][9][10] The main disadvantages are erosion of the clinician-patient relationship and concerns around quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…The reported advantages include lower financial costs, high patient satisfaction, better rural access, decreased waiting times and fewer missed appointment. [2][3][4][5][6][7] There is less available evidence from primary care; however, there are positive findings in primary care chronic disease management. [8][9][10] The main disadvantages are erosion of the clinician-patient relationship and concerns around quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…6 This situation favours the use of new information and communication technologies (ICTs) aimed at improving professional qualifications and achieving greater equality in the provision of healthcare services. 7,8,9 Experiences in several countries have shown that investments in PHC made with the goal of improving physical resources and professional qualifications lead to a significant improvement in the population's health indicators. 10,11,12 The constant updating of scientific knowledge requires continued professional education to ensure the quality of care.…”
Section: Introductionmentioning
confidence: 99%
“…Rural population are reported to have a poor quality of life, access to oral health, and oral health status [ 30 34 ]. People living in rural areas may also be less satisfied with their oral health care because of poor access to oral health care services that, in turn, could be influenced by several factors such as low socioeconomic status, geographic remoteness, shortages of dental professionals, lack of public transportation and limited dental insurance coverage [ 28 , 35 – 38 ]. According to the Canadian Census 2016, about 19.4% of all Quebecers live in rural areas [ 39 ].…”
Section: Introductionmentioning
confidence: 99%